Bayes Estimation of Shape Parameter of Length Biased Weibull Distribution - Rao, Arun Kumar; Pandey, Himanshu (Universitas Muhammadiyah Mataram, 2021)
In this paper, length biased Weibull distribution is considered for Bayesian analysis. The expressions for Bayes estimators of the parameter have been derived under squared error, precautionary, entropy, K-loss, and Al-Bayyati’s loss functions by using quasi and gamma priors.